O cenário educacional: o professor e a tecnologia da informação e comunicação diante das mudanças atuais - Mainardi, Andreia; Muller, Liziany Medeiros; Rech, Aline Pereira de Arruda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The objective of this study it evaluates the integration of Information and Communication Technologies (ICTs) as tools to support teaching in the School Hall Elementary School Octavian Passion Rabbit. The exploratory research methodology was qualitative and he data evaluated from the survey type questionnaire for teachers soft the school. It is noteworthy that before the questionnaire was watching the video Education Network (http://www.youtube.com/watch?v=AJlP6aeR6Lo). The results point to the challenge of educating for innovation and change, planning and deploying dynamic teaching both proposals regarding the adequate training of teachers in planning and methodology to promote student motivation and promotion of the teaching-learning linked the socio-historical conceptions of education, in the cognitive, ethical, political, scientific, cultural, recreational and aesthetic. This study highlights the need for change in the role of teacher, qualifying them to seek ways to act pedagogically with ICT for teachers and students to know, interpret, use, reflect critically technology to not be dominated by promoting the integral development of man, innovation, renewal of education, making critical and reflective teaching, thus allowing the qualitative improvement of the educational process.